2016
DOI: 10.17511/ijmrr.2016.i09.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of laryngoscopic view, intubation difficulty and sympathetic response during direct laryngoscopy in sniffing position versus simple head extension: a clinical comparative study

Abstract: Background: Proper position of the head and the neck is important for optimizing laryngoscopic view and for ease of endotracheal intubation.We compared two different positions, sniffing position and simple head extension during direct laryngoscopy on the basis of laryngoscopic view, intubation difficulty and sympathetic response. Methodology: One hundred twenty patients of age group 20-50 years, scheduled for elective surgeries under general anaesthesia were divided into two equal groups in a randomized fashio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Most of these studies have confirmed the superiority of SP over simple head extension. [ 4 5 ] Thus, it has become clear that head elevation or neck flexion improves the glottic view. However, how much elevation of head provides the best view is not yet clear.…”
mentioning
confidence: 99%
“…Most of these studies have confirmed the superiority of SP over simple head extension. [ 4 5 ] Thus, it has become clear that head elevation or neck flexion improves the glottic view. However, how much elevation of head provides the best view is not yet clear.…”
mentioning
confidence: 99%